ผลของ IBA ต่อการสร้างหน่อและการเจริญเติบโตของกล้วยหอมทองที่ขยายพันธุ์โดยวิธีผ่าเหง้า - หาระโคตร, พรชัย; พลจันทร์, ปริญญา; พวงจิก, ธัญพิสิษฐ์ (Thai Journal of Science and Technology, 2019)
Abstract The objective of this experiment was to study effect of indole-3-butyric acid (IBA) on rooting, sucker production and growth of Kluai Hom-Thong [Musa (AAA group)], which was propagated through rhizome-cutting method. The experiment was conducted at the experiment field, Department of Agricultural Technology, Thammasat University, Rangsit Centre. The experiment was carried out by using CRD with four replications. Six different concentrations of IBA including 500, 1,000, 1,500, 2,000 and 2,500 ppm, compared with non-IBA treatment were studied. The results showed that banana sucker survival rate from all treatments were not significantly different (100 %). However, mean times to shoot emerging, root length, plant height and diameter, and number of leave/plant were statistically different. The control treatment was found the greatest of mean times to shoot emerging (23.36 days). However, 1,000 ppm IBA gave the highest of root length (14.50 cm), plant diameter (1.78 cm) and number of leave/plant (3.5 leaf/plant). Additionally, the results showed that banana rhizome treated with high concentrations of IBA decreased shoot emerging time and plant height. Therefore, the Kluai Hom-Thong propagation through rhizome-cutting treated with 1,000 ppm IBA was appropriate to induce sucker production and growth. Keywords: Kluai Hom-Thong; propagation; growth regulator; indole-3-butyric acid